Pengembangan Multimedia Pembelajaran Interaktif untuk Meningkatkan Motivasi dan Hasil Belajar Siswa pada Materi Kesetimbangan Kimia SMA - Lola Fibriani; Muhammad Damris; Risnita Risnita (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2014)
The purpose of this study was to develop a multimedia learning to improve student motivation and outcomes in studying chemical equilibrium. Development of interactive multimedia development model is adapted from Lee and Owens, the steps were analysis, design, development, implementation, and evaluation. The Media developed combined texts, animations, videos, references, summaries, profiles, pictures and narration to visualization abstract concepts of chemical equilibrium. After validation and trials at small group the media was used in a teaching class.  It shoved that the media may be helpful for low motivations students in studying chemical equilibrium and improved students achievement.